Earnings and occupational attainment: immigrants and the native born - Barry R. Chiswick; Paul W. Miller (Institute for the Study of Labor (IZA), 2007)
This paper examines the determinants of occupational attainment and the impact of occupation on earnings. Results for both the native born and foreign born are presented, and these provide insights as to the earnings penalties associated with the less-than-perfect international transferability of human capital skills. It shows that around 50 percent of the earnings gains associated with years of schooling derives from inter-occupational mobility. When occupation is held constant, there is a large increase in the effect on earnings of pre-immigration labor market experience for the foreign born, but little change in either the payoff to labor market experience for the native born, or in the premium for post-arrival labor market experience for the foreign born. The estimates of the models of occupational attainment show that years of schooling, and, among the foreign born, proficiency in English, are the key factors determining access to high-paying occupations. Labor market experience has little effect on occupational outcomes among the native born. However, evaluated at 10 years, foreign labor market experience has a modest negative impact on current occupational status. Examination of this negative effect using quantile regression shows that it is concentrated among those in high status jobs.
urn:nbn:de:101:1-20080414144
Keywords: 330; Migranten; Qualifikation; Erwerbsverlauf; Sprache; Humankapital; Beruf; Lohnstruktur; USA